Effect of Banana Types on Oven Drying Process for Crispy Banana Production - Saputri, Arum Dyah; Amalia, Rizka; Yulianto, Mohamad Endy; Paramita, Vita (Journal of Vocational Studies on Applied Research, 2020)
This study aims to determine the effect of moisture and drying rate on Kepok and milk banana species, on the production process of crispy banana. An electric oven was used to examine the drying process at variable temperatures of 70 ºC, 80 ºC and 100 ºC with slices of 1 mm, 2 mm, 3 mm and 4 mm thickness. The results showed that the lowest moisture content and maximum drying rate obtained in Kepok was at a temperature of 100ºC, namely 69.167% and 0.045 grams/minute respectively. Meanwhile, for milk banana, the lowest moisture and the maximum drying rate was obtained at a temperature of 100 ºC, namely 68.167% and 0.042 grams/minute respectively. Furthermore, the organoleptic test results showed that kepok and milk banana experienced browning at 100 ºC, but did not at 70 ºC and 80 ºC with a thickness of 1mm, 2mm and 3mm. In addition, the pore structure of both bananas expanded, while the structure of the bananas appeared bigger after drying.